Effect of aminophylline on brain tissue oxygenation in patients with chronic obstructive lung disease. Issue 12 (December 1992) - Nishimura, M; Suzuki, A; Yoshioka, A; Yamamoto, M; Akiyama, Y; Miyamoto, K; Kishi, F; Kawakami, Y
Abstract : BACKGROUND: It is known that theophylline reduces cerebral blood flow in humans. To quantitatively assess the possible adverse effect of theophylline on brain tissue oxygen tension (PO2) due to decreased cerebral blood flow, two sets of experiments were conducted in mildly hypoxaemic patients with chronic obstructive lung disease. METHODS: Firstly, internal jugular venous PO2 (PjO2) was measured simultaneously with arterial and mixed venous blood PO2 (PaO2 and PvO2) during right heart catheterisation in 10 subjects (mean PaO2 73 mm Hg; conversion factor: 10 mm Hg = 1.33 kPa)) before and after intravenous infusion of aminophylline (6 mg/kg). The PjO2 and PvO2 were considered to reflect the average tissue PO2 for the brain and for the whole body respectively. Secondly, the relation between PaO2 and PjO2 over a wide range, with the PaCO2 similar to that in the first study, was investigated in a different group of 12 subjects by stepwise changes in inspiratory gas composition. RESULTS: The mean PjO2 decreased by as much as 6 mm Hg 15 minutes after an infusion of aminophylline, whereas PaO2 stayed at the same level and PvO2 showed only a small decrease. The low PjO2 value of 29 (SD 6) mm Hg with aminophylline in the first study was similar to the PjO2 value of 30 (2) mm Hg obtained during severe hypoxia (PaO2 45 mm Hg) in the second study. The coefficient of oxygen delivery for the brain decreased by 29% with aminophylline treatment, but did not change significantly during severe hypoxic challenge. CONCLUSIONS: These data suggest that an infusion of aminophylline lowers brain tissue PO2 appreciably when given to mildly hypoxaemic patients with chronic obstructive lung disease.